Relationship between Capillary Wettability, Mass, and Momentum Transfer in Nanoconfined Water: The Case of Water in Nanoslits of Graphite and Hexagonal Boron Nitride - Smith, Lois; Wei, Zixuan; Williams, Christopher D.; Chiricotto, Mara; Pereira da Fonte, Claudio; Carbone, Paola (ACS applied materials & interfaces, 2024)
The flow of water confined in nanosize capillaries is subject of intense research due to its relevance in the fabrication of nanofluidic devices and in the development of theories for fluid transport in porous media. Here, using molecular dynamics simulations carried out on 2D capillaries made up of graphite, hexagonal boron nitride (hBN) and a mix of the two, and of sizes from subnanometer to few nanometers, we investigate the relationship between the wettability of the wall capillary, the water diffusion, and its flow rate. We find that the water diffusion is decoupled from its flow properties as the former is not affected either by the height or chemistry of the capillary (except for the subnanometer slits), while the latter is dependent on both. The capillaries containing hBN show a reduced flow rate compared to those that are purely graphitic, likely due to the high friction coefficient between water and hBN. Such resistance to the flow is, however, at its maximum in the smallest capillary and lower for larger ones. Finally, we show that the flow rate values obtained from the Hagen–Poiseuille theory are almost always smaller than those obtained from simulations, indicating that either the slip length or the viscosity of nanoconfined water could be substantially different from the bulk values.